Factors affecting dental services accessibility - Miran Forjanič; Valerij Dermol; Valentina Prevolnik Rupel (Nurses and Midwives Association of Slovenia, 2019)
Introduction: Access to dental services is a basic right included in the compulsory health insurance for patients and thus an important part of the healthcare system in Slovenia. The purpose of this research was to identify and explore the factors that have the greatest impact on the accessibility of dental services from the perspective of the system stakeholders in Slovenia. Methods: A qualitative study was conducted based on the focus group method. The focus group consisted of relevant system stakeholders, namely two representatives of the regulator, provider and payer, a total of six participants. A thematic analysis was carried out in order to identify the patterns and themes within thequalitative data obtained. Results: The results of the focus group revealed the views of system stakeholder on the accessibility of dental services in Slovenia. According to the system stakeholders' perspective, accessibility of dental services in Slovenia is not optimal and significant changes in terms of financing and organisation are required. Discussion and conclusion: We found that the lack of adequate human resources, insufficient health insurance and payment for services are the crucial factors in providing adequate access to dental health in Slovenia. In order to increase its accessibility, the dental programme needs to be expanded and the number of teams for its implementation increased.